2011
DOI: 10.1016/j.drup.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib or gefitinib for the treatment of relapsed platinum pretreated non-small cell lung cancer and ovarian cancer: A systematic review

Abstract: Copyright and moral rights to this thesis/research project are retained by the author and/or other copyright owners. The work is supplied on the understanding that any use for commercial gain is strictly forbidden. A copy may be downloaded for personal, non-commercial, research or study without prior permission and without charge. Any use of the thesis/research project for private study or research must be properly acknowledged with reference to the work's full bibliographic details.This thesis/research projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 115 publications
(142 reference statements)
0
47
0
Order By: Relevance
“…Although the RR was not different according to the treatment timing in this study, some studies have shown that the RR to gefitinib in chemotherapy-naive patients was higher than that in patients with prior chemotherapy [22,23]. However, no general cross-resistance has been demonstrated and EGFR-TKIs are suitable for the treatment of patients with NSCLC who have been treated with platinum-based therapy, particularly those with EGFR mutation-positive tumors [24]. Several studies, including our data, showed no statistical difference between chemotherapy-naive patients and patients who had received prior chemotherapy in terms of PFS or time to progression [10,22].…”
Section: Univariate and Multivariate Analysismentioning
confidence: 51%
“…Although the RR was not different according to the treatment timing in this study, some studies have shown that the RR to gefitinib in chemotherapy-naive patients was higher than that in patients with prior chemotherapy [22,23]. However, no general cross-resistance has been demonstrated and EGFR-TKIs are suitable for the treatment of patients with NSCLC who have been treated with platinum-based therapy, particularly those with EGFR mutation-positive tumors [24]. Several studies, including our data, showed no statistical difference between chemotherapy-naive patients and patients who had received prior chemotherapy in terms of PFS or time to progression [10,22].…”
Section: Univariate and Multivariate Analysismentioning
confidence: 51%
“…EGFR-TKIs have limited but valuable activity in previously treated NSCLC patients. EGFR mutation (exons [18][19][20][21], increased EGFR copy number or increased expression of EGFR/phosphorylated EGFR (pEGFR) leads to significantly improved response rates to EGFR-TKIs in patients with pretreated NSCLC [2]. These biomarkers are not mutually exclusive, and the expression of EGFR may predict EGFR gene status (including copy number and mutation) to some extent [3].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with low levels of ERCC1, high ERCC1 levels were associated with shorter survival and poor prognosis in patients with nonsmall-cell carcinoma, which was not related to clinical therapy (Milovic-Kovacevic et al, 2011;Murphy and Stordal, 2011;Rubatt et al, 2012). High expression level of ERCC1 is one of the predictive indicators for poor effects of platinum-based chemotherapy (Li et al, 2014).…”
Section: Discussionmentioning
confidence: 99%